1940
DOI: 10.1002/ajpa.1330270225
|View full text |Cite
|
Sign up to set email alerts
|

The brachial plexus in Macacus rhesus, compared with man

Abstract: FIFTEEN FIQURESSince the brachial plexus in monkeys has not heretofore been examined in series large enough for statistical treatment, we feel that we are fortunate in being able to offer in the present report a thorough study of the plexus in Nacacus rhesus (Pithecus rhesus after Elliot, '13 ; Macaca mulatta after Miller, '33). This study is based on dissections of right and left plexuses in 150 specimens, i.e., a total of 300 plexus dissections. Each dissection and record are our own work, from which it foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1948
1948
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Thus, such a pattern forming the left MN with two distinct inputs and running on either side of the axillary artery resembles felids (Getty et al, 1986). Our initial thoughts of the existence of a common trunk with the MCN (homolog of the lateral cord of the BP in primates) was not the case (Chase & DeGaris, 1940; Ghoshal & Magilton, 1972; Souza et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, such a pattern forming the left MN with two distinct inputs and running on either side of the axillary artery resembles felids (Getty et al, 1986). Our initial thoughts of the existence of a common trunk with the MCN (homolog of the lateral cord of the BP in primates) was not the case (Chase & DeGaris, 1940; Ghoshal & Magilton, 1972; Souza et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the case described here, the communicating branch ran from the MN to the MCN on the left side, and in both directions on the right side. The communicating branch from the MN to the MCN is normally seen in macaques (Chase & DeGaris, 1940; Ohashi, 1966), and as a variation in humans (Iwamoto et al, 1990; Maeda et al, 2009). Sharp et al (1991), in an electrophysiological study of a muscular branch to the brachialis muscle, found evoked potential from ventral branches of spinal nerves T1 and T2, suggesting that nerve fibres to the brachialis muscle may not have descended directly from the MCN but through the MN and the communicating branch between the two nerves (Sharp et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the musculocutaneous nerve sends out the communicating branch to the median nerve in dogs (Allam et al, 1952;Hashimoto, 1960;Sisson and Grossman, 1961;Miller et al, 1969;Zietzschmann et al, 1974). The median nerve sends out the branch to the musculocutaneous nerve in macaques (Howell and Straus, 1933;Chase and DeGaris, 1940;Sugiyama, 1960;Urbanowicz, 1964;Ohashi, 1968). In general, an independent musculocutaneous nerve is absent in Artiodactyla and Perissodactyla (Raimers, 1925-a; Sisson and Grossman, 1961;Arlamowska-Palider, 1970;Zietzschmann et al, 1974).…”
Section: Discussionmentioning
confidence: 99%